Speaking with other animals through intuitive interspecies communication: towards cognitive and interspecies justice - Barrett, M.J.; Hinz, Viktoria; Wijngaarden, Vanessa; Lovrod, Marie (Edward Elgar Publishing, 2021)
Intuitive interspecies communication (IIC) involves detailed, non-verbal and non-physical communication between humans and other animals using a wide range of intuitive capacities. IIC and the growing number of animal communicators who practice it professionally have been virtually ignored in academic research in animal geographies and beyond. In response to calls for epistemological innovation and ontological diversity as well as cognitive and interspecies justice, we introduce IIC as a valuable process to deepen understandings of animals’ perspectives and standpoints. We then discuss lessons learned as researchers and learners who are committed to advancing capacities to conduct research with animals, rather than on them. We offer some reflexive cautions, then posit that IIC can provide an important methodological pathway to engaging animals as active partners in knowledge production. More equitable interspecies collaborations in academic research may be facilitated through the translation capacities of animal communicators.